PANCASILA SEBAGAI LANDASAN ILMU UNTUK MEWUJUDKAN KEADILAN SOSIAL DI INDONESIA - Hulu, Dinis Putra (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Pancasila is the foundation of the Indonesian state, playing a role in shaping national and state life. As the ideology of Indonesia, Pancasila not only serves as a guideline but also as a scientific foundation for creating social justice, particularly in Indonesia. This article aims to analyze how Pancasila, especially its fifth principle, can serve as a guideline for realizing social justice in Indonesia. Using a qualitative approach, this study explores the values of Pancasila in the context of economics, education, health, and sustainable development. The results of the study indicate that the fifth principle, “Social Justice for All Indonesians,” embodies principles of justice that can be applied to public policy, equitable resource distribution, and the elimination of social inequalities among the people. Moreover, Pancasila serves as a moral foundation for law enforcement that protects the rights of all citizens without discrimination among groups and supports the development of science oriented toward equitable and wise welfare. The integration of Pancasila’s moral values into various fields can create harmony between scientific development and the needs of Indonesian society. However, the successful implementation of Pancasila as a scientific foundation for realizing social justice requires the commitment of all national elements to use it as a guide in decision-making and policymaking. By making Pancasila the foundation and guideline for building a scientific paradigm, it is hoped that a fair, prosperous, and civilized society can be achieved.